Farmers’ Response to the LEISA Approach - Arief Rahma Hakim; Asro Laelani Indrayanti1; Yulia Yustha; Aulia Rahma Balina (Proceeding International Conference on Digital Education and Social Science, 2024)
In response to changes in government policy regarding fertilizer subsidies, the introduction and training of the LEISA approach were carried out in Sidodadi Village, Maliku District, Pulang Pisau Regency. Sidodadi Village, formerly known as Pangkuh 6B, is an ex-transmigration area where most of the community members are horticultural crop farmers. The activity stages included Socialization, Training, Assistance in technology implementation, Monitoring and Evaluation, and Program Sustainability. After the activities were completed, a questionnaire was distributed to assess farmers' responses and the prospects of the LEISA approach in Sidodadi Village. Measurement results showed that most farmers (56.67%) were aware of the government’s policy changes regarding subsidized fertilizers. Observations revealed that after the LEISA training, there was an increase in the application of various techniques, including producing fertilizer from rice washing water (56.63%), organic fertilizer from household waste (63.33%), fertilizer from husk charcoal (46.67%), fertilizer from livestock urine (13.33%), and the use of self-made fertilizers (13.37%). Although there was a shift in farmers’ perceptions towards the LEISA approach, their dependence on factory-made fertilizers remained quite high. However, despite this dependency, the future of LEISA implementation in Sidodadi Village has good prospects due to increased awareness and application of self-made fertilizers.